Acute Capsaicin Analog supplementation improves 400 m and 3000 m running time-trial performance - Costa, L. A.; de Freitas, M. C.; Cholewa, J.; Nakamura, F.; Panissa, V.; Silva, V. E. Lopes de Moura e Silva Vilton Emanoel Lopes de Moura e; Sá, A. M. B; Queiroz, P. A.; Galan, S. L.; Santos, M. A. P; Zanchi, N. E.; Lira, F. S.; et al. (International Journal of Exercise Science, 2020)
Objectives: Performance in running-based sport depends on the ability to perform repetitive high intensity muscle contractions. Previous studies have shown that capsaicin analog (CAP) (i.e. Capsiate) supplementation may improve this performance. The purpose of this study was to investigate the acute effect of CAP supplementation on short (400 m) and middle distance (3000 m) running time-trial performance, maximum heart rate (HR), and rate of perceived exertion (RPE). Methods: Twelve physically active men completed four randomized, double-blind trials: CAP condition (12 mg) or a placebo condition. Forty-five minutes after supplementation, the participants performed a 400- or 3000-meter running time trial. Time (in seconds) was recorded. HR was analyzed at rest and immediately post-exercise, and RPE was collected immediately after exercise. Results: For both the 400 m time-trial (CAP = 66.4 + 4.2 sec vs Placebo = 67.1 + 4.8 sec, p = 0.046) and the 3000 m time-trial (CAP = 893.9 ± 46.8 sec vs Placebo = 915.2 ± 67.6 sec, p = 0.015), the time in seconds was significantly less in the CAP compared to placebo conditions. There were no statistically significant differences for HR and RPE in any condition. Conclusion: In summary, acute CAP supplementation improved 400 m and 3000 m running time-trial performance in a distance-dependent way but without modifying the HR and RPE.